תשובה:
א) # 2 (x + 2) ^ 2-3 #
ב) # 10- (x-2) ^ 2 #
הסבר:
א) # 2x ^ 2 + 16x + 5 #
# => 2 x ^ 2 + 8x + 5/2 #
# צבע (אדום) + צבע (כחול) b + ^ 2 = a + 2 + צבע (ירוק) 2 צבע (אדום) צבעי אקור (כחול) b + b ^ 2 #
# => 2 צבע אדום x ^ 2 + צבע (ירוק) 2 * צבע (כחול) 4 צבע (אדום) x + צבע (כחול) 4 ^ 2-4 ^ 2 + 5/2
# => 2 צבע (אדום) x ^ 2 + צבע (ירוק) 2 * צבע (כחול) 4 צבע (אדום) x + צבע (כחול) 4 ^ 2) -16 + 5/2
# => 2 (x + 4) ^ 2-32 / 2 + 5/2 #
# => 2 (x + 4) ^ 2-27 / 2 #
# => 2 (x + 4) ^ 2-Cancel2 * 27 / Cancel2 #
# => 2 (x + 4) ^ 2-27 #
ב) # 6 + 4x-x ^ 2 #
# => - 1 * x ^ 2-4x-6 #
# => - 1 * צבע (אדום) x ^ 2 צבע (ירוק) 2 * צבע (כחול) 2 צבע (אדום) x + צבע (כחול) 2 ^ 2-2 ^ 2-6
# => - 1 * צבע (אדום) x ^ 2 צבע (ירוק) 2 * צבע (כחול) 2 צבע (אדום) x + צבע (כחול) 2 ^ 2) -4-6
# => - 1 * (צבע (אדום) x צבע (כחול) 2) ^ 2-10 #
# => - (x-2) ^ 2 + 10 #
# => 10- (x-2) ^ 2 #
בהנחה שאנחנו צריכים לפתור את המשוואות שמשלימות את שיטת הריבוע.
א) # 2x ^ 2 + 16x + 5 = 0 #
# => x ^ 2 + 8x + 5/2 = 0 #
# => x ^ 2 + 2 * x * 4 + 4 ^ 2-4 ^ 2 + 5/2 = 0 #
# => (x + 4) ^ 2-16 + 5/2 = 0 #
# => (x + 4) ^ 2-27 / 2 = 0 #
# => (x + 4) ^ 2 = 27/2 #
# => x + 4 = pmsqrt27 / 2 #
# => x = -4pm (3sqrt3) / 2 #
(ב) # 6 + 4x-x ^ 2 = 0 #
# => 6 + 2 ^ 2-2 ^ 2 + 2 * x * 2-x ^ 2 = 0 #
# => 10- (2 ^ 2-2 * x * 2 + x ^ 2) = 0 #
# => (x-2) ^ 2 = 10 #
# => x-2 = pmsqrt10 #
# => x = 2pmsqrt10 #